What digital competencies should teachers possess to teach educational cybersecurity to students in schools? Design and validation of a teacher competency ccale - De-la-Flor-Bancalero, Pablo; Guillen-Gámez, Francisco David (Springer, 2026)
The purpose of this study was to design and validate an instrument to assess the teaching competencies necessary to didactically teach cybersecurity and safe Internet use in educational contexts. Specifically, the following phases were addressed: content validity, Comprehension validity, construct validity through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), as well as convergent and discriminant validity, and reliability analysis through various statistical coefficients. The instrument was structured in five dimensions: (1) Basic knowledge about identification and prevention of digital threats, (2) Protection of personal information in digital environments, (3) Secure use of hardware, software and browsers, (4) Password management and authentication, and (5) Continuous updating and training of teachers in cybersecurity. The sample consisted of 754 in-service teachers from different educational levels (Early Childhood Education, Primary, Secondary, Vocational Training, and Adult Education) from all over Spain. The results showed adequate fit indices for the factorial model (KMO = 0.965; χ2 = 18,410.047; p < .001), total explained variance of 82.54% and excellent internal consistency with values ​​greater than 0.70. In addition, satisfactory convergent validity (AVE > 0.50) and discriminant validity (MSV < AVE) values ​​were confirmed. With all these coefficients, the instrument is valid and reliable for diagnosing teachers’ self-perceived level of cybersecurity and safe and responsible internet use teaching, with a total of 15 items classified into five latent factors. The instrument offers a practical tool to identify in-service teachers’ training needs in educational cybersecurity and to support the planning of professional development and specific training programs based on empirical evidence.
Keywords: Profesores - Formación profesional; Seguridad informática; Teaching competencies; Didactic teaching; Cybersecurity education; Safe use of the internet; Teachers; Scale